New developments in MRI: System characterization, technical advances and radiotherapy applications. (October 2021) - Mazzoni, Lorenzo Nicola; Bock, Michael; Levesque, Ives R.; Lurie, David J.; Palma, Giuseppe
Abstract: A Special Issue of Physica Medica – European Journal of Medical Physics, focused on some important points of contact between the world of magnetic resonance and that of medical physics, was published during 2021. This Editorial describes and comments on the content of this Focus Issue, which contains articles from leading groups invited by the Guest Editors.